One-pot migration-formylation of benzyl aryl ethers under duff reaction condition - Chavan, Subhash P.; Lasonkar, Pradeep B. (Tetrahedron Letters, 2013)
A one-pot migration-formylation of benzyl aryl ethers under Duff reaction condition is described. The reaction was performed with HMTA (hexamethylene tetramine) and TFA (trifluoroacetic acid). Under the optimal reaction conditions, a variety of Bn and PMB ethers underwent ortho rearrangement. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Benzyl aryl ethers; Duff reaction; Hexamethylene tetramine; One-pot; ortho Rearrangement

Simple synthesis of the novel antihistaminic drug olopatadine hydrochloride - Chavan, Subhash P.; Lasonkar, Pradeep B. (Synthesis-Stuttgart, 2013)
A new alternative route for the synthesis of olopatadine is described. The present strategy involves a Lewis acid mediated ring opening of a cyclic ether to introduce 3-(dimethylamino)propylidene group as the side chain.
Keywords: antihistaminic drugs; chelates; Lewis acids; spiro compounds; zinc

Facile and convenient synthesis of (+/-)-Biotin via MgCl2/Et3N-mediated C-C coupling and mitsunobu reaction - Chavan, Subhash P.; Chavan, Prakash N.; Lasonkar, Pradeep B.; Khairnar, Lalit B.; Kadam, Appasaheb L. (Synlett, 2014)
A synthesis of (+/-)-biotin is described starting from simple starting materials viz. cyclohexanone and amino malonic acid ester. The key steps involved are MgCl2/Et3N coupling of amino malonic acid ester derivative and acid chloride, Mitsunobu reaction, ozonolysis, Staudinger reduction, novel urea formation, and subsequent dibenzylation. This approach is economical and involves high-yielding steps and simple reaction conditions.
Keywords: Appel reaction; biotin; Mitsunobu reaction; Ozonolysis; Staudinger reduction

Synthesis of 3-azidopiperidine skeleton employing ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether: total synthesis of d-2 receptor agonist (+/-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Lasonkar, Pradeep B.; Gonnade, Rajesh G. (Organic letters, 2018)
The total synthesis of (+/-)-quinagolide, which is a D-2 receptor agonist, was accomplished via a ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether route. Key features of the synthesis include Claisen rearrangement, PPTS (pyridinium p-toluene-sulfonate)-catalyzed one-pot acetal deprotection, followed by a diastereoselective Henry reaction, which enables construction of the required trans ring junction and CAN-mediated regioselective azidoalkoxylation of enol ether. The PPTS-catalyzed intramolecular diastereoselective Henry reaction to fix three contiguous stereocenters on tetrahydronaphthalene and the first-of-its-kind synthesis of the 3-azidopiperidine skeleton, using a CAN -mediated regioselective azidoalkoxylation of enol ether, are important findings of the present work.